Advanced High Strength Steel in Auto Industry: an Overview - Baluch, N.; Udin, Z. M.; Abdullah, C. S. (Engineering, Technology & Applied Science Research, 2014)
The world’s most common alloy, steel, is the material of choice when it comes to making products as diverse as oil rigs to cars and planes to skyscrapers, simply because of its functionality, adaptability, machine-ability and strength. Newly developed grades of Advanced High Strength Steel (AHSS) significantly outperform competing materials for current and future automotive applications. This is a direct result of steel’s performance flexibility, as well as of its many benefits including low cost, weight reduction capability, safety attributes, reduced greenhouse gas emissions and superior recyclability. To improve crash worthiness and fuel economy, the automotive industry is, increasingly, using AHSS. Today, and in the future, automotive manufacturers must reduce the overall weight of their cars. The most cost-efficient way to do this is with AHSS. However, there are several parameters that decide which of the AHSS types to be used; the most important parameters are derived from the geometrical form of the component and the selection of forming and blanking methods. This paper describes the different types of AHSS, highlights their advantages for use in auto metal stampings, and discusses about the new challenges faced by stampers, particularly those serving the automotive industry.